Self‐Delivering Microstructured Iota Carrageenan Spray Inhibits Fibrosis at Multiple Length Scales - Robinson, Thomas E.; Brunet, Mathieu Y.; Chapple, Iain; Heagerty, Adrian H. M.; Metcalfe, Anthony D.; Grover, Liam M. (Advanced NanoBiomed Research (Online), 2023)
Fibrotic diseases account for 45% of all deaths in the developed world, and progressive scarring conditions, such as dystrophic epidermolysis bullosa (EB), result in a significant reduction in quality of life. There is thus a need for novel approaches in fibrosis prevention. Herein, it is shown that iota carrageenan, a low‐cost, regulatory approved polysaccharide, is effective at preventing scarring by inhibiting collagen fibrillogenesis, abrogating the transforming growth factor beta 1 (TGFβ1) pathway, and lubricating the epithelium. It is demonstrated that iota carrageenan, and other anionic polysaccharides, can prevent collagen fibril formation, a key step in scar formation. It also binds TGFβ1 to prevent myofibroblast transdifferentiation, evidenced by a significant reduction in both transcription and translation of collagen 1 and alpha smooth muscle actin. Iota carrageenan may be formulated as a microparticle suspension, to allow spraying for even coverage on hard‐to‐reach anatomical sites, like the oral mucosa. This formulation provides good lubrication, to reduce the shear forces that initiate the progressive oral scarring in EB. This study not only provides a novel therapy for fibrosis prevention, but also demonstrates the potential of self‐delivering immunomodulatory polysaccharides as a safe, cost‐effective, and stable platform, which can be more easily translated for clinical benefit.